Dynamics of Nodes: Adaptation of Interior Places in a Historic Waterfront Community for Sustainability - Laiprakobsup, Thanapan; Laiprakobsup, Narongpon (UI Scholars Hub, 2025)
This study aims to investigate environmental interiority and urban conditions which promote adaptations of nodes as foci of place in the historic, suburban waterfront community. Nodes, existing as strategic places as public activity settings, on the other hand, have been barely examined in terms of the dynamic transition of interior places among urbanisation. The study argues that nodal adaptations taking up dynamic development play crucial functional roles in sustaining a waterfront community in connection with the implementation of place resources and accessible opportunities of new transportation networks. Nodal adaptations lead to the emergence of new functions and place identity in the community. This study employs multiple case-study methods to examine adaptive nodes in suburban waterfront communities along Klong Om-Non in Nonthaburi Province, Thailand. The study finds that nodal adaptations can be categorised into communal, cultural, and commercial nodes. Roles, place resources, and potential accessibility to communities contribute to the variation of nodal adaptations. Nodal adaptations are associated with the novel meaning of Klong Om-Non’s communities from an agricultural base to a sanctuary for urbanites. Consequently, community development programmes need to consider how designing and programming nodes of place could integrate with environmental identity and modification, that is, meaningful to people in the community and prospective visitors. Understanding adaptive nodes as convivial interior places in communities and collaborating with sustainable creativity will contribute to the urban rehabilitation of historic communities.